The impact of Mn nonstoichiometry on the oxygen mass transport properties of La0.8Sr0.2MnyO3±δ thin films. (1st October 2022) - Chiabrera, Francesco M; Baiutti, Federico; Börgers, Jacqueline M; Harrington, George F; Yedra, Lluís; Liedke, Maciej O; Kler, Joe; Nandi, Pranjal; Sirvent, Juan de Dios; Santiso, Jose; López-Haro, Miguel; Calvino, José J; et al.
Abstract: Oxygen mass transport in perovskite oxides is relevant for a variety of energy and information technologies. In oxide thin films, cation nonstoichiometry is often found but its impact on the oxygen transport properties is not well understood. Here, we used oxygen isotope exchange depth profile technique coupled with secondary ion mass spectrometry to study oxygen mass transport and the defect compensation mechanism of Mn-deficient La0.8 Sr0.2 Mn y O3± δ epitaxial thin films. Oxygen diffusivity and surface exchange coefficients were observed to be consistent with literature measurements and to be independent on the degree of Mn deficiency in the layers. Defect chemistry modeling, together with a collection of different experimental techniques, suggests that the Mn-deficiency is mainly compensated by the formation of La Mn × antisite defects. The results highlight the importance of antisite defects in perovskite thin films for mitigating cationic nonstoichiometry effects on oxygen mass transport properties.